Scientific method applied to failure analysis on engineering components. - Masriera, Lucio (2013)
Trabajo presentado en el 13º International Congress of Science and Technology of Metallurgy of Materials, SAM - CONAMET 2013. Puerto Iguazú, Misiones. 2013